HUBUNGAN TINGKAT KEROHANIAN DAN PENCAPAIAN AKADEMIS SISWA DI SMA X - Alan Hubert Sanger; Juwinner Dedy Kasingku; Randa Frizky Karu (Universitas Pahlawan Tuanku Tambusai, 2022)
This study focuses on students' spiritual level and academic achievement. The instrument used is a questionnaire adopted from Umboh and Tebo (2015) regarding the level of spirituality. The total participants were 110 students from classes Xa, Xb, Xc, and Xd SMA X using the convenience sampling method. The results of this study revealed that the spiritual level of students and the level of academic achievement of students were in the high category. And there is a significant relationship between the level of student spirituality and student academic achievement. So, the higher the spiritual level of students, the higher their academic achievement of students. As a recommendation, because schools are educational institutions, teachers should pay attention to the spiritual development of students by involving students in spiritual activities. Keywords: spiritual level, academic achievement, student